Chaperone-Like Activity of a Bacterioferritin Comigratory Protein from Thermococcus kodakaraensis KOD1 - P. Pham, Bang; Jia, Baolei; Lee, Sangmin; Ying, Sun; M. Kwak, Jae; Cheong, Gang-Won (Protein and Peptide Letters, 2015)
Peroxiredoxins (Prxs) are ubiquitous and conserved proteins that can catalyze the reduction of inorganic and organic hydroperoxides to protect against damage by reactive oxygen species. In this study, a Prx subfamily member, and specifically a bacterioferritin comigratory protein from hyperthermophilic Thermococcus kodakaraensis KOD1 (TkBcp), was overexpressed, purified and characterized. Based on the conserved cysteine (Cys) residues in its amino acids sequence, TkBcp can be grouped into 1-Cys Prx family. Size exclusion chromatography analysis showed that TkBcp exists in three oligomeric forms: 700 kDa, 70 kDa, and 20 kDa. The peroxidase function was found to predominate in the lowmolecular- weight (MW) form, whereas the high-MW complex has the chaperone function. Oxidative reagents caused the protein structure of TkBcp to shift from low-MW form to high-MW complexes, whereas reducing reagents caused a shift in the reverse direction. Furthermore, the high-MW form of TkBcp preferred to tightly bind DNA. The relationship of TkBcp with other homologs was also examined.
Keywords: Thermococcus kodakaraensis KOD1